The role of institutions in supporting coastal communities at risk from climate change: A case study of Buffeljagsbaai, South Africa - Ismail, Alveena Aziz (Department of Environmental and Geographical Science, 2022)
Coastal communities are dependent on marine resources which provide their households with food and income. Fishing communities are considered the poorest of the poor and face many challenges that render them vulnerable. Climate change further exacerbates these challenges making fishing communities amongst the most vulnerable groups to coastalrelated risks including sea-level rise and extreme weather events. Often, these fishing communities are neglected and excluded from policies and decisions concerning coastal and fisheries management as well as climate change adaptation. Management is often fragmented across institutions that are mandated to govern coastal resources and coastal areas. The study uses Buffeljagsbaai as a case study lens to understand the nature of coastal risks faced by marginalized coastal communities on the south west coast of the Western Cape Province in South Africa. It investigates how coastal risks related to climatic, social and economic factors affect livelihoods and examines the roles of various institutions in responding to, engaging with, and supporting the Buffeljagsbaai community as they confront coastal risks. Qualitative data collection methods were used to address the objectives of this study and included semi-structured interviews with community members and officials in relevant government institutions, as well as facilitated a community focus group discussions and participant observation. The analysis revealed coastal- related risks have a major impact on the livelihoods of coastal communities. However, over time, the community has diversified their livelihoods in order to adapt to these risks. Findings reveal that women in the case study site have developed more diverse livelihoods making them more resilient to climate change than the fishermen, who are largely dependent on fishing and are consequently more vulnerable to coastal- related risks. In addition, the community has not been given access to coastal resources and where permits have been issued, these have many restrictions. As a result, the community has resorted to “poaching” to provide food and an income for their households. The government institutions that are responsible for various aspects of resource management, disaster risk reduction, poverty alleviation and socio-economic development, are largely absent in the community. The lack of government presence in and support to this community, also referred to as limited statehood, has led to distrust and the reliance on non-governmental organisations and other stakeholders to fill this gap.